Effects of iron doping at 55 °C on LiNi0.85Co0.10Al0.05O2 - Kim, Cheong; Park, Tae-Jun; Min, Song-Gi; Yang, Su-Bin; Son, Jong-Tae (Journal of the Korean Physical Society, 2014)
Iron-doped LiNi 0.85 Co 0.1 Al 0.05 O 2 cathode materials with an α -NaFeO 2 structure were synthesized by using co-precipitation and ball-mill methods. The structures of samples were confirmed by using X-ray diffraction, and the sizes and the morphologies of the particles were observed by using scanning electron microscopy. The initial discharge capacity value of the pristine cathode material was 206 mAh/g, but the Fe-doped LiNi 0.85 Co .1 Al 0.05 O 2 cathode material delivered an initial discharge capacity of 215 mAh/g. The capacity retentions of the Fe-doped LiNi 0.85 Co 0.1 Al 0.05 O 2 cathode material were higher than those of the pristine cathode material at 55 °C. The lithium diffusion coefficients of the pristine material and the Fe-doped LiNi 0.85 Co 0.1 Al 0.05 O 2 cathode material were calculated to be 4.5 × 10 −17 and 4.0 × 10 −17 cm 2 /s, respectively, after cycling at 55 °C. The Fe-doped LiNi 0.85 Co 0.1 Al 0.05 O 2 cathode material has the highest lithium diffusion coefficient and its electrochemical properties are better than those of the pristine material at high temperatures.